Injury Epidemiology - Li, Guohua
The editorial mission of Injury Epidemiology is to advance the science and practice of injury prevention and control through timely publication and dissemination of peer-reviewed research. Injury Epidemiology aims to be the premier venue for communicating epidemiologic studies of unintentional and intentional injuries, including, but not limited to, morbidity and mortality from motor vehicle crashes, drug overdose/poisoning, falls, drowning, fires/burns, iatrogenic injury, suicide, homicide, assaults, and abuse. Relevant studies are investigations designed to understand the magnitude, distribution, determinants, causes, prevention, diagnosis, treatment, prognosis, and outcomes of injuries in specific population groups, geographic regions, and environmental settings (e.g., home, workplace, transport, recreation, sports, and urban/rural). Of special interest are studies that strengthen the scientific foundation of injury prevention and control and generate objective and practical knowledge to reduce injury morbidity and mortality on a population level. Priority consideration will be given to manuscripts that feature contemporary theories and concepts, innovative methods, and novel techniques as applied to injury surveillance, risk assessment, development of effective interventions, and program/policy evaluation.